Brucella pinnipedialis in hooded seal (Cystophora cristata) primary epithelial cells - Larsen, Anett Kristin; Godfroid, Jacques; Nymo, Ingebjørg Helena (Acta Veterinaria Scandinavica, 2016)
License:Creative Commons Attribution 4.0 International License (http://creativecommons.org/licenses/by/4.0/) Background: Marine Brucella spp. have been isolated from numerous pinniped and cetacean species, but pathological findings in association with infection with Brucella pinnipedialis in pinnipeds have been sparse. The capacity of brucellae to survive and replicate within host macrophages underlies their important ability to produce chronic infections, but previous work has shown that B. pinnipedialis spp. are rapidly eliminated from hooded seal (Cystophora cristata) alveolar macrophages. Results: To investigate if multiplication could take place in other hooded seal cell types, primary epithelial cells were isolated, verified to express the epithelial marker cytokeratin and challenged with three different strains of B. pinnipedialis; B. pinnipedialis sp. nov., B. pinnipedialis hooded seal strain B17, and B. pinnipedialis hooded seal strain 22F1. All strains were steadily eliminated and the amounts of intracellular bacteria were reduced to less than one-third by 48 h post infection. Intracellular presence was verified using immunocytochemistry. Conclusions: So far, intracellular multiplication in seal cells has not been documented for B. pinnipedialis. The lack of intracellular survival in macrophages, as well as in epithelial cells, together with the fact that pathological changes due to B. pinnipedialis infection is not yet identified in seals, suggests that the bacteria may only cause a mild, acute and transient infection. These findings also contribute to substantiate the hypothesis that seals may not be the primary host of B. pinnipedialis and that the transmission to seals are caused by other species in the marine environment.